2021
DOI: 10.1109/tim.2020.3010193
|View full text |Cite
|
Sign up to set email alerts
|

The Possibilistic Kalman Filter: Definition and Comparison With the Available Methods

Abstract: The Kalman filter is a commonly used algorithm for predicting the state variables of a system. It is based on the model of the system and some measurements (observed over time), which are characterized by their own uncertainty.This paper defines a possibilistic Kalman filter, whose main feature is to predict the values of the state variables and the associated uncertainty, also when uncertainty contributions of non-random nature are present. This possibilistic Kalman filter is defined in the mathematical frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Other more specific applications are present in the more recent literature, like for instance the generalization of Bayes' theorem in the possibility domain [19,20] or the realization of a possibilistic Kalman filter [21,22], thus showing the versatility of the RFV approach. Obtained results when case studies B and C are considered: GUM approach (red lines), Monte Carlo approach (blue lines), RFV approach (cyan lines).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other more specific applications are present in the more recent literature, like for instance the generalization of Bayes' theorem in the possibility domain [19,20] or the realization of a possibilistic Kalman filter [21,22], thus showing the versatility of the RFV approach. Obtained results when case studies B and C are considered: GUM approach (red lines), Monte Carlo approach (blue lines), RFV approach (cyan lines).…”
Section: Discussionmentioning
confidence: 99%
“…Other more specific applications are present in the more recent literature, like for instance the generalization of Bayes' theorem in the possibility domain [19,20] or the realization of a possibilistic Kalman filter [21,22], thus showing the versatility of the RFV approach.…”
Section: Figure 13mentioning
confidence: 99%
“…given by [31] () =− =1 log 2 (12) And () and () represent nonspecificity and strife of possibility distribution [21], respectively, given by…”
Section: Klir's Uncertainty-preservation Transformationmentioning
confidence: 99%
“…As an alternative method to fuzzy sets for handling fuzzy uncertainty, possibility theory has in recent decades received extensive attention [1][2][3][4][5][6][7][8][9][10][11][12][44][45][46]. It was lately demonstrated that probability and possibility are customized for the measure of randomness and fuzziness, respectively [6].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative method to fuzzy sets for handling fuzzy uncertainty, possibility theory has in recent decades received extensive attention [1][2][3][4][5][6][7][8][9][10][11][12][44][45][46]. It was lately demonstrated that probability and possibility are customized for the measure of randomness and fuzziness, respectively [6].…”
Section: Introductionmentioning
confidence: 99%